The Patterns of Women's Leadership to Create Gender Equality in Building a Sustainable Organization - Indira Puspa Gustiah; Nawangsari , Lenny Christina (International Journal of Law Policy and Governance, 2023)
Purpose –Leadership in building organizations by men and women has its own strengths and weaknesses, but the lack of women's leadership in Indonesia represents gender equality has not been achieved. This study aims to determine the pattern of women's leadership in Indonesia to create gender equality in building a sustainable organization Methodology/approaches – This type of research uses a social research strategy with a simple mix method approach. The target population in this study were members who worked in various private organizations in Bekasi district with female leaders with a sample of 50 respondents. The data statistical method used is descriptive statistics and Partial Least Square (PLS). Findings –This result was confirmed by a data source triangulation approach, namely by interviewing three existing data sources. The results of this study indicate that the pattern of female leadership has not been able to mediate the concept of ideal leadership or the concept of ideal gender equality towards sustainable organizations.However, this research also shows that the concept of ideal leadership and the concept of ideal gender have a positive and significant effect on leadership patterns Novelty/value – women's leadership patterns reflect the concept of ideal leadership and the concept of ideal gender equality needed in a leadership that can lead an organization. Keywords: Leadership pattern, women, gender equality, sustainable organization